2005
DOI: 10.1002/pmic.200401092
|View full text |Cite
|
Sign up to set email alerts
|

Autopolyploidy in cabbage (Brassica oleracea L.) does not alter significantly the proteomes of green tissues

Abstract: Polyploidization is a major evolutionary process in eukaryotes. In plants, genetic and epigenetic changes occur rapidly after formation of allopolyploids. Hybridization, rather than genome doubling itself, is considered as the main cause for the resulting differential gene expression. We studied the consequences of genome doubling alone in an autopolyploid model, by comparing two-dimensional gel electrophoresis (2-DE) gels of haploid, diploid, and tetraploid Brassica oleracea cabbages. Two fully homozygous lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
1
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 60 publications
2
58
1
6
Order By: Relevance
“…The latter category, detected due to the reproducibility of the 2-DE method, shows that many subtle adjustments of gene expression occur in amphiploids. Hybridization rather than genome doubling appeared to be the primary cause of gene expression repatterning, in accordance with previous experiments demonstrating that the stem proteome of B. oleracea HDEM was not significantly altered by autopolyploidy (Albertin et al 2005). The small effect of genome doubling on gene regulation in autotetraploids was recently demonstrated in another model system: Wang et al (2006) compared diploid and tetraploid A. thaliana and showed that autopolyploidization did not induce genomewide nonadditive regulation.…”
Section: Discussionsupporting
confidence: 69%
“…The latter category, detected due to the reproducibility of the 2-DE method, shows that many subtle adjustments of gene expression occur in amphiploids. Hybridization rather than genome doubling appeared to be the primary cause of gene expression repatterning, in accordance with previous experiments demonstrating that the stem proteome of B. oleracea HDEM was not significantly altered by autopolyploidy (Albertin et al 2005). The small effect of genome doubling on gene regulation in autotetraploids was recently demonstrated in another model system: Wang et al (2006) compared diploid and tetraploid A. thaliana and showed that autopolyploidization did not induce genomewide nonadditive regulation.…”
Section: Discussionsupporting
confidence: 69%
“…Qualitative gene expression changes, such as complete gene silencing and derepression, have been commonly observed in allopolyploidy systems. In contrast, the results from the present study as well as several previous investigations indicate that newly synthesized autopolyploids undergo much fewer gene expression changes (Albertin et al 2005;Wang et al 2006). A recent microarray-based study on both allopolyploids and autopolyploids derived from A. thaliana clearly demonstrated that newly synthesized allopolyploids experience far greater global gene expression changes than do newly synthesized autopolyploids (Wang et al 2006).…”
Section: Discussioncontrasting
confidence: 56%
“…The effect of ploidy per se can only be assessed among a series of homozygous plants at different ploidy levels. There have been relatively few studies dedicated to elucidating the consequences of autopolyploidization on gene expression (Guo et al 1996;Galitski et al 1999;Albertin et al 2005;Auger et al 2005;Storchova et al 2006;Wang et al 2006). Thus, the genetic impact imposed by ploidy alteration remains elusive.…”
mentioning
confidence: 99%
“…The few studies that have applied modern proteomic techniques in a comparative fashion have found little variation among species (Albertin et al 2005(Albertin et al , 2006(Albertin et al , 2007. In contrast to the expectations implied by this work as well as the high level of coding sequence conservation among the species studied, the cotton seed proteomes analyzed here display extraordinary variation.…”
Section: Biased Accumulation Of D-genome Proteins In Polyploid Cottonmentioning
confidence: 99%
“…As proteins represent the key players in cellular activities, characterizing the proteome using appropriately targeted approaches constitutes an important component of the evolutionary analysis of polyploidy and its consequences. A classical proteomic technique, two-dimensional gel electrophoresis (2-DE), has the potential to assess the expression patterns of proteins displayed by polyploid species relative to their diploid progenitors, as demonstrated in Brassica (Albertin et al 2005(Albertin et al , 2006(Albertin et al , 2007. This technique allows the resolution of hundreds of protein spots within a single gel, which are accessible to identification through mass spectrometry (MS) analysis; moreover, some post-translational modifications corresponding to protein activities can be inferred via interpretation of the on-gel and MS properties.…”
mentioning
confidence: 99%